IMPACT OF DIGITAL MARKETPLACES ON MICRO-ENTREPRENEURSHIP GROWTH IN EBONYI STATE (IJOVTECH, 2026)
The emergence of the digital marketplace has transformed the market of micro-entrepreneurship especially in developing markets such as in Ebonyi State of Nigeria. The research examines how digital marketplaces lead to the development of the micro-enterprises within the state of Ebonyi using primary data collection method in the form of the surveys that were conducted with 300 micro-enterprises in the state. The study combines the theoretical considerations of the Technology Acceptance Model and the Diffusion of Innovations theory in a study that investigates the impact of the following factors (perceived ease of use, perceived usefulness, and innovativeness) on acceptance and further success of a business. Results show that there is a substantial positive effect of digital marketplace adoption on the growth in revenues, market coverage, and operational efficiency of the micro-entrepreneurs where average sales showed to be 45 percent higher among adopters than among non-adopters every month. The demographic characteristics indicate that the respondents were mostly women (62%), ranging in age between 25-44 years (68%), with secondary education levels (55%), which also characterized the rural and agrarian population of the state. However, barriers that were observed to challenge digital inclusion were limited internet access, digital literacy, and infrastructural deficits, although there were opportunities that could be exploited to implement policies that would lead to inclusive digital integration. The study helps to fill the gap in the entrepreneurship literature, as it exemplifies the dynamics of context-specifics in sub-Saharan Africa, as well as combines the old ground-laying theories on entrepreneurial orientation with the recent studies of digital transformation. Digital training and infrastructure investments to facilitate the development of micro-entrepreneurship are some of the recommendations. This study highlights how digital platforms can change how poverty alleviation and economic development take place in the hitherto underserved regions.